NeuroBlu: a natural language processing (NLP) electronic health record (EHR) data analytic tool to generate real-world evidence in mental healthcare - R. Patel; S.N. Wee; R. Ramaswamy; S. Thadani; G. Guruswamy; R. Garg; N. Calvanese; M. Valko; A. Rush; M. Rentería; J. Sarkar; S. Kollins (European Psychiatry, 2022)
Introduction